Implementation of the project "Health Steps - education and learning as a determinant of a healthy and open society" as an example of a holistic approach to a healthy lifestyle for children and young people - Anna Brzęk; Agnieszka Białek-Dratwa; Marcin Drzazga; Tomasz Wojtasik; Regina Wysocka; Elżbieta Szczepańska; Agata Kiciak; Justyna Skolik; Barbara Kowalska; Oskar Kowalski (Śląski Uniwersytet Medyczny w Katowicach, 2024)
The unique project "Health Steps - education and learning as a determinant of a healthy and open society" was implemented as part of the "Social Responsibility of Science" programme funded by the Ministry of Education and Science. This innovative initiative was led by the Medical University of Silesia in Katowice (SUM), the Regional In-Service Teacher Training Centre "Metisˮ and the Iskierka Foundation. The project aimed to increase the responsibility of teachers and legal guardians of healthy children and to instil in each group the awareness that taking care of physical health, mental health, and proper nutrition significantly impacts the quality of life. The project identifies eight broad tasks to enhance knowledge, practical skills, and social competencies in three thematic areas: physioprophylaxis, diet prevention, as well as mental health and oncology prevention. As part of physio prophylaxis, educational films on correct posture were realised, preventive posture examinations were conducted among children, and training workshops on ergonomics and adopting correct body positions while learning and playing were held. During the stage related to diet prevention, screening tests for overweight and obesity were carried out, including anthropometric tests, i.e. measurement of body height, body weight and body composition analysis among children. Eating behaviour and attitudes towards nutrition among children and their parents were studied, and a dietary intervention combined with nutrition education was implemented. Workshops conducted for teachers on the educational method of drama and supervision were aimed at enhancing educators' competence in using these methods in health education. Extending care to children and adolescents is justified because their lifestyle habits depend on the environment in which they are raised (parents, teachers, peers). Informed participation in such projects allows them to take conscious control of their health in collaboration with an interdisciplinary team of professionals.